Kreasi Sponge Cake dari Bubuk Wortel dan Bubuk Labu Kuning Ditinjau dari Uji Organoleptik - Wangke, Kenzie Felicia; Minantyo, Hari (JURNAL GASTRONOMI INDONESIA, 2025)
This study aims to explore the use of carrot powder and pumpkin powder as substitutes for flour in making sponge cake, with a focus on organoleptic testing. Sponge cake is a popular pastry, but its conventional version raises health concerns. Carrot and pumpkin were chosen because they are rich in beta-carotene and other essential nutrients. The experiment was conducted with five different concentrations of flour substitution (0%, 25%, 50%, 75%, 100%) and two preparation methods: steaming and baking. Organoleptic tests were carried out to assess the quality of the product based on color, aroma, taste, and texture, with 90 panelists from Surabaya providing feedback on the sponge cake samples. The results of the organoleptic testing showed that the formulations with 25% (25% carrot powder and 75% pumpkin powder) and 50% (50% carrot powder and 50% pumpkin powder) flour substitution using carrot and pumpkin powders had the best results, with no significant difference in taste, aroma, and texture compared to the control sponge cake (no substitution). These formulations were the most favored by the panelists, showing the potential of using local ingredients as an alternative to wheat flour. This research is expected to offer innovation in the food industry, support food diversification by utilizing local products, and reduce dependence on imported wheat flour.